Pilot study to understand and compare challenges being faced in reporting of transfusion reactions in various types of blood banks enrolled under Haemovigilance Programme of India - Rayaz Ahmad Bhat; Vishal Tiwari; Satyajeet Singh; Ruchi Rao; Akash Chaudhary; Akanksha Bisht (Asian Journal of Transfusion Science)
BACKGROUND: Hemovigilance has become one of the important quality check systems of blood transfusion process, but under/non-reporting of transfusion-associated adverse reactions despite the presence of reporting systems emphasize the need to understand the challenges being faced in active reporting of adverse transfusion reactions. AIM: To identify and document the possible factors leading to under-reporting and impacting the quality of blood transfusion reactions being submitted under Haemovigilance Programme of India (HvPI). SETTINGS AND DESIGN: This was a cross-sectional, observational type study, carried out in six blood banks, two each of government, private, and stand-alone sectors in Delhi National Capital Region enrolled under HvPI. MATERIALS AND METHODS: The study was carried out for a period of 6 months with a-month residence in each blood bank. During this period, data related to adverse transfusion reactions and their reporting were collected using a designed data collecting form and a validated questionnaire from all the six blood banks. STATISTICAL ANALYSIS USED: MS Excel Ver. 2007 was used for compilation and descriptive analysis of collected data, and SPSS Ver. 25.0 was used for determining the Cronbach’s alpha for the questionnaire which was statistically significant (α > 0.7). RESULTS: In a period of 6 months, a total of 5136 blood products were issued from these blood banks along with 5136 reaction reporting forms, but only 515 transfusion reaction report forms were returned to these blood banks. It was found that each blood bank faces some challenges with respect to identifying and reporting adverse transfusion reactions. CONCLUSION: Addressing the gaps identified during this study will result in robust hemovigilance system in our country and having reliability of data being reported under HvPI.